Search for dilepton resonances in pp collisions at √s=7 TeV with the ATLAS detector - Anduaga, Xabier Sebastián (2011)
This Letter reports on a search for narrow high-mass resonances decaying into dilepton final states. The data were recorded by the ATLAS experiment in pp collisions at ffiffi s p ¼ 7 TeV at the Large Hadron Collider and correspond to a total integrated luminosity of 1.08 ð1:21Þ fb-1 in the e+e- (μ+ μ-) channel. No statistically significant excess above the standard model expectation is observed and upper limits are set at the 95% C.L. on the cross section times branching fraction of Z0 resonances and Randall-Sundrum gravitons decaying into dileptons as a function of the resonance mass. A lower mass limit of 1.83 TeV on the sequential standard model Z0 boson is set. A Randall-Sundrum graviton with coupling k=M Pl ¼ 0:1 is excluded at 95% C.L. for masses below 1.63 TeV.